If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3p + -6p = -3 Combine like terms: 3p + -6p = -3p 6 + -3p = -3 Solving 6 + -3p = -3 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3p = -3 + -6 Combine like terms: 6 + -6 = 0 0 + -3p = -3 + -6 -3p = -3 + -6 Combine like terms: -3 + -6 = -9 -3p = -9 Divide each side by '-3'. p = 3 Simplifying p = 3
| -4c=72 | | 37-4x=46+1x | | 133=-21(1-8m)+7 | | 3x-40=2x-20 | | (-6)-q=-38 | | Tan2x=-5/3 | | 5(m-3)=7m-17 | | 6a(3+4a)= | | 4/5•2 | | P-32=-75 | | 4z/-16=-7 | | 12z-2=12z+8 | | Y+(-38)=-23 | | 10x+14+9x-63=540 | | 230=s+144 | | -189=-7(-3p+6) | | (-9)-p=-23 | | 10x+14+9x-63=180 | | 3(x-1)-1=3+2(x-3) | | -2(y-5)=8 | | 33=n*3 | | (G-3)0.4=30 | | 25h=-700 | | 2.3r-7=1.3r-7 | | -2(y+-5)=8 | | 13*5=y | | -3=7+2v | | 42*6=x | | M=26+18 | | -2+2u=6 | | 3(6x+4)-3x+8=49 | | 2j=3j+9 |